An audit of paediatric epilepsy care. Issue 2 (1st August 1998) - Webb, David W; Coleman, Helen; Fielder, Allison; Kennedy, Colin R
Abstract : Basic standards for the process of paediatric epilepsy care were identified and applied in a clinical audit; findings were presented and the audit repeated. Standards agreed related to quality of correspondence, prescribing practice, appropriateness of drug monitoring, use of neuroimaging, and quality of requests for electroencephalography (EEG). Parent satisfaction with staff courtesy, doctor communication, and clinic visits were also assessed. In the second audit prescribing practice and appropriateness of drug monitoring had improved, but quality of patient correspondence and requests for EEG were unchanged. In both periods of care many parents were dissatisfied with the quality and amount of information provided about epilepsy. Standards of care for the medical management of children with epilepsy can be agreed and used to identify achievable improvements in that care.